Study guides

☆☆

Q: How do you do 3X squared plus 18 plus 9?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

The given expression can be simplified to: 8x squared +9

57

(x - 6)(x + 9)

-51

9x2 + 3x / 3x equals (3x + 1).9x2 + 3x divided by x is 9x + 3 , and then divided by 3 yields the 3x +1.

Related questions

The given expression can be simplified to: 8x squared +9

-27

4x+6-7x+9=18-3x+15=18-3x=3x=-1

9x2 - 6xy + y2 - 81 = (3x - y)2 - 81 = (3x - y - 9)*(3x - y + 9)

Divide the entire equation by 9. (9x2 + 27x + 18)/9 would then be 9(x2 + 3x +2) The factors of this equation would be 9(x + 1)(x + 2)

9x2 - 6xy + y2 - 81 = (3x - y)2 - 92 = (3x - y - 9)(3x - y + 9)

27-9 =18. 18/3 =6

(8x + 9)(3x^2 - 1)

(5x 2 - 8x + 1) + (2x 2 - 4x - 11)

57

(x - 6)(x + 9)

5x^2 + 6x + 9 + (?) = -x^2 +3x + 3 (?) = -5x^2 -6x - 9 -x^2 +3x + 3 = -6x^2 -3x -6 Ans: -6x squared +3x -6

People also asked